Social influence, agent heterogeneity and the emergence of the urban informal sector - García-Díaz, César; Moreno-Monroy, Ana I. (Physica A, 2012)
We develop an agent-based computational model in which the urban informal sector acts as a buffer where rural migrants can earn some income while queuing for higher paying modern-sector jobs. In the model, the informal sector emerges as a result of rural–urban migration decisions of heterogeneous agents subject to social influence in the form of neighboring effects of varying strengths. Besides using a multinomial logit choice model that allows for agent idiosyncrasy, explicit agent heterogeneity is introduced in the form of socio-demographic characteristics preferred by modern-sector employers. We find that different combinations of the strength of social influence and the socio-economic composition of the workforce lead to very different urbanization and urban informal sector shares. In particular, moderate levels of social influence and a large proportion of rural inhabitants with preferred socio-demographic characteristics are conducive to a higher urbanization rate and a larger informal sector. ► Migration based on wage differentials and social influence leads to informality. ► Social influence and preferential hiring explain informal sector size differences. ► Moderate social influence significantly increases the urban informal sector. ► Under strong social influence urbanization and informality rates are lower.